Outcome of Locally Delivered Antibiotics via Bone Cement in Infective Nonunion, Chronic Osteomyelitis and Joint infections, A Case Series (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To determine the outcome of locally delivered antibiotics via bone cements in infective non-union, chronic osteomyelitis and joint infectionsMethods: The study was conducted between January 2016 to June 2017. Patient with chronic osteomyelitis and infective non-union of long bones were chosen. Debribement / sequestrectomy and antibiotics beads placement was done in chronic osteomyelitis. In selected cases antibiotic, coated nail was put and in arthroplasties, antibiotic was added to spacer as prophylaxis to infection. The infected bone was scraped out leaving an opening in the bone. The antibiotic beads were then packed into the opening and the wound was closed for 4-5 weeks when they were removed. Bone was fixed in case of instability, when there were no signs of infections per operatively.Results: Twenty-seven (90%) out of 30 patients showed no signs of recurrence of osteomyelitis at the mean of 15 months follow up. Infection subsided in 2 out of remaining 3 patients, with re- debridement and beads and 1 patient did not show any sign of improvement even after second procedure. No significant complication was noted during the study.Conclusion: Antibiotics loaded Beads in the treatment of chronic osteomyelitis are safe and effective. Its advantages include lower cost, low systemic effects of the drug, shorter hospital stay and high concentrations of antibiotics at the site of infection.